Numerical performance evaluation of plain fin tube heat exchanger under frosty conditions - Hussein, Amar Ali (2010)
Heat exchangers are devices used to transfer thermal energy between two fluids or more, existing in different temperatures. Heat exchangers exist in many types and shapes, so they can be found in many applications. Plain fin and circular tube heat exchangers are commonly used in refrigerators and air-conditioning devices. In this type of heat exchanger, surface’s temperature falls below the freezing temperature of water vapor existed in the air flows across these exchangers. The low temperature makes this vapor accumulates on exchanger’s surfaces and forms frost. This degrades the performance of these exchangers by decreasing the heat transfer rate as frost works as thermal resistance. As a result to this problem the refrigerator or the air-condition needs more time to reach the desired point of cooling and this makes penalty in saving energy of electricity. In the present research, numerical study has been adopted to analyze and find way to enhance the performance of the plain fin and circular tubes heat exchangers. Three-dimensional simulations have been conducted to analyze the effects of three different collar diameters (7.53, 8.51 and 10.23 mm) on the heat transfer rate and pressure drop as first objective. The effects of three different half-transverse tube pitches to longitudinal tube pitch ratio Tp on the heat transfer rate and pressure drop have been also analyzed. Model geometries have been drawn and meshed in GAMBIT 2.3 and simulations have been performed in commercial CFD code FLUENT 6.3. Results showed that heat transfer rate has increased as the collar diameter increased with penalty in the increasing of pressure drop. It was also found that the heat transfer rate has increased as Tp ratio increased, but the pressure drop increased for Tp = 0.5 and decreased for Tp = 1. Therefore, to enhance performance without changing the size of the exchanger can be achieved by increasing the collar diameter with consideration of the pressure drop limitations. Instead, if the free space considered in the device has flexibility, the enhancement can be achieved by increasing the transverse tube pitch length.